Exploring the impact of magnetic fields on biomass production efficiency under aerobic and anaerobic batch fermentation of Saccharomyces cerevisiae - Sincak, M; Turker, M; Derman, Ü C; Erdem, A; Jandacka, P; Luptak, M; Luptakova, A; Sedlakova-Kadukova, J (Scientific reports, 2024)
In this work, the effect of moderate electromagnetic fields (2.5, 10, and 15 mT) was studied using an immersed coil inserted directly into a bioreactor on batch cultivation of yeast under both aerobic and anaerobic conditions. Throughout the cultivation, parameters, including CO2 levels, O2 saturation, nitrogen consumption, glucose uptake, ethanol production, and yeast growth (using OD 600 measurements at 1-h intervals), were analysed. The results showed that 10 and 15 mT magnetic fields not only statistically significantly boosted and sped up biomass production (by 38-70%), but also accelerated overall metabolism, accelerating glucose, oxygen, and nitrogen consumption, by 1-2 h. The carbon balance analysis revealed an acceleration in ethanol and glycerol production, albeit with final concentrations by 22-28% lower, with a more pronounced effect in aerobic cultivation. These findings suggest that magnetic fields shift the metabolic balance toward biomass formation rather than ethanol production, showcasing their potential to modulate yeast metabolism. Considering coil heating, opting for the 10 mT magnetic field is preferable due to its lower heat generation. In these terms, we propose that magnetic field can be used as novel tool to increase biomass yield and accelerate yeast metabolism.
Keywords: Magnetic field; Glycerol; anaerobióza; Anaerobiosis; fermentace; glycerol; Nitrogen; dusík; Yeast; aerobióza; Aerobiosis; Anaerobic; Batch fermentation; ethanol; magnetické pole; glukosa; biomasa; Oxygen; kyslík; Fermentation; Glucose; Metabolism acceleration; Saccharomyces cerevisiae; Bioreactors; Ethanol; Biomass; Magnetic Fields; bioreaktory; Aerobic